2023
DOI: 10.1038/s41467-023-36896-0
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock molecule REV-ERBα regulates lung fibrotic progression through collagen stabilization

Abstract: Molecular clock REV-ERBα is central to regulating lung injuries, and decreased REV-ERBα abundance mediates sensitivity to pro-fibrotic insults and exacerbates fibrotic progression. In this study, we determine the role of REV-ERBα in fibrogenesis induced by bleomycin and Influenza A virus (IAV). Bleomycin exposure decreases the abundance of REV-ERBα, and mice dosed with bleomycin at night display exacerbated lung fibrogenesis. Rev-erbα agonist (SR9009) treatment prevents bleomycin induced collagen overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…123 Conversely, REV-ERBα agonists suppress TGF-β1 (transforming growth factor β1)-induced fibroblast-to-myofibroblast transition and profibrotic phenotype. 124,125 Consistent with the knowledge that the CLOCK/BMAL1 heterodimer is immediately upstream of REV-ERBα, mice deficient for BMAL1 in the proximal tubule exhibit increased renal fibrosis in response to stress. 126 Collectively, these observations highlight that critical fibroblast functions are under circadian control.…”
Section: Impact Of Cell-autonomous Circadian Clocks On Cardiovascular...mentioning
confidence: 78%
“…123 Conversely, REV-ERBα agonists suppress TGF-β1 (transforming growth factor β1)-induced fibroblast-to-myofibroblast transition and profibrotic phenotype. 124,125 Consistent with the knowledge that the CLOCK/BMAL1 heterodimer is immediately upstream of REV-ERBα, mice deficient for BMAL1 in the proximal tubule exhibit increased renal fibrosis in response to stress. 126 Collectively, these observations highlight that critical fibroblast functions are under circadian control.…”
Section: Impact Of Cell-autonomous Circadian Clocks On Cardiovascular...mentioning
confidence: 78%
“…Another enzyme tested in this study is lysyl oxidase, a copper-dependent amine oxidase that helps to stabilize the ECM structure via crosslinking collagen and elastin fibers [ 38 ]. Upregulation of lysyl oxidase has been identified from the fibrotic lesion in lung fibrosis patients and in bleomycin-induced lung fibrotic injury [ 39 ]. Upregulated lysyl oxidases during fibrogenesis drive severe crosslinking of collagen and elastin fibers, preventing degradation of fibrous matrix and contributing to irreversible scarring [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Novel therapies to treat pulmonary fibrosis and other fibrotic diseases are an unmet clinical need that has to be addressed. Emerging studies using preclinical models, in vitro and in vivo, demonstrated the potential of circadian clock-based therapeutics such as Rev-erbα agonists that directly or indirectly target TGFβ signaling to mitigate the progression of PF [ 9 , 10 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence supports the role circadian clock proteins in the pathobiology of chronic lung diseases including IPF [ 7 10 ]. Circadian clocks are endogenous oscillators that control 24-h physiological and behavioral processes in mammals, regulated externally by Zeitgebers (time of feeding, exercise, sleep-wake cycle, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation